Monographic of the journal "Forms of resistance and modes of education". Persevere in criticism: a form of resistance - Mainer Baqué, Juan (Avances en Supervisión Educativa, 2014)
Monográfico de la revista: Formas de resistencia y modos de educaciónCoordinadoresJuan Mainer y Javier GurpeguiEditorial Diada (2013)ISSN 1697-3127 ISBN 978-84-96723-39-9